Dynamic risk assessment method of urban drought based on water balance and optimal allocation analysis. Issue 7 (March 2020) - Sun, Keke; Xu, Jijun; Yao, Liqiang; Yuan, Zhe; Pan, Deng; Qu, Yanping; Miao, Henglu
Abstract: Based on the analysis of driving factors of urban drought, this paper adopts different methods of water balance and drought identification for different water supply sources, such as local water storage and transit runoff. By calculating the city water shortage rate and frequency under different water supply conditions and combining with the benefit analysis model of water supply for each water using sectors, the relationship curve between water loss and water shortage rate for each major industry in cities and towns is established. Based on the dynamic optimal distribution of water shortage for each industry and the forecast results of precipitation and runoff, the dynamic loss and risk assessment method for urban drought with different water supply sources is put forward. Taking Qidong County and the towns of Hengyang City along the Xiangjiang River as examples, the model method is validated. The results show that there is a power function relationship between the urban drought loss and the water shortage during the drought period, the models may provide theoretical reference for optimizing urban water allocation management and making urban drought resistance plan.